Obstetric factors and different causes of special educational need: retrospective cohort study of 407 503 schoolchildren. Issue 3 (27th November 2012) - Mackay, DF; Smith, GCS; Dobbie, R; Cooper, S‐A; Pell, JP
<x xml:space="preserve">Abstract</x> Objective To determine whether relationships with gestational age and birthweight centile vary between specific causes of special educational need (SEN). Design Retrospective cohort study. Setting Scotland. Population A cohort of 407 503 schoolchildren. Methods Polytomous logistic regression was used to examine the risk of each cause of SEN across the spectrum of gestation at delivery and birthweight centile, adjusting for potential confounding factors. Main outcome measures Crude and adjusted odds ratios and confidence intervals. Results Of the 19 821 children with SEN, 557 (2.8%) had sensory impairments, 812 (4.1%) had physical or motor disabilities, 876 (4.4%) had language impairments, 2823 (14.2%) had social, emotional, or behavioural problems, 7018 (35.4%) had intellectual disabilities, 4404 (22.2%) had specific learning difficulties, and 1684 (8.5%) autistic spectrum disorder (ASD). Extreme preterm delivery (at 24–27 weeks of gestation) was a strong predictor of sensory (adjusted OR 23.64, 95% CI 12.03–46.45), physical or motor (adjusted OR 29.69, 95% CI 17.49–50.40), and intellectual (adjusted OR 11.67, 95% CI 8.46–16.10) impairments, with dose relationships across the range of gestation. Similarly, birthweight below the third centile was associated with sensory (adjusted OR 2.85, 95% CI 2.04–3.99), physical or motor (adjusted OR 2.47, 95% CI 1.82–3.37), and intellectual (adjusted OR 2.67, 95% CI 2.41–2.96) impairments. Together, gestation and birthweight centile accounted for 24.0% of SEN arising from sensory impairment, 34.3% arising from physical or motor disabilities, and 26.6% arising from intellectual disabilities. Obstetric factors were less strongly associated with specific learning difficulties and social or emotional problems, and there were no significant associations with ASD. Conclusions The association between gestation and birthweight centile and overall risk of SEN is largely driven by very strong associations with sensory, physical or motor impairments, and intellectual impairments.